CICLO REPRODUCTOR DE UTA STEJNEGERI SCHMIDT 1921 (SAURIA: PHRYNOSOMATIDAE) EN DUNAS DEL BOLSÓN DE MAPIMÍ; DURANGO; MÉXICO - Gadsden, Héctor; Méndez De La Cruz, Fausto R.; Gil Martínez, Rosalina (Instituto de Ecología, A.C., 2004)
The reproductive cycle of the lizard Uta stejnegeri Schmidt 1921 (previously Uta stansburiana stejnegeri Schmidt 1921) was determined using data obtained from field caught individuals at the Biosphere Reserve of Mapimí, Durango, México. During 1990 monthly samples of this species were collected from sand dunes. Males reached sexual maturity at 45.0 mm snouth–vent length (SVL); females reached sexual maturity at 40.0 mm SVL. The reproductive cycles of both sexes were synchronous. Significant variation in testes mass was determinated by ANCOVA and males reached maximal testes mass between December-February; testes began to decrease in July, reaching minimum mass in September. The monthly percentage of non-vitellogenic follicles, vitellogenic follicles and oviductal eggs was recorded for females. Enlarged vitellogenic follicles first appeared during mid-January in females. These showed bimodal presence of eggs in oviducts between February and May and in July. Mean clutch size based on oviductal eggs counts was 2.8 ± 1.1. Clutch size was positively correlated with female body size. Most of the annual rainfall ocurrs during summer, and we suggest that offspring production is timed to the best season to promote juvenile growth and survivorship. We found similarities between this reproductive cycle and those previously reported for U. stansburiana from the United States.